Fibroblast growth factor-21, energy balance and obesity. (15th December 2015) - Giralt, Marta; Gavaldà-Navarro, Aleix; Villarroya, Francesc
Abstract: Fibroblast growth factor (FGF)-21 is an endocrine member of the FGF family with healthy effects on glucose and lipid metabolism. FGF21 reduces glycemia and lipidemia in rodent models of obesity and type 2 diabetes. In addition to its effects improving insulin sensitivity, FGF21 causes weight loss by increasing energy expenditure. Activation of the thermogenic activity of brown adipose tissue and promotion of the appearance of the so-called beige/brite type of brown adipocytes in white fat are considered the main mechanisms underlying the leaning effects of FGF21. Paradoxically, however, obesity in rodents and humans is characterized by high levels of FGF21 in the blood. Some degree of resistance to the actions of FGF21 has been proposed as part of the endocrine alterations in obesity. The resistance in adipose tissue from obese rodents and patients is likely attributable to abnormally low levels of the FGF co-receptor β-Klotho, required for FGF21 cellular action. However, native FGF21 and FGF21 derivatives retain their healthy metabolic and weight-loss effects when used as pharmacological agents to treat obese rodents and humans. FGF21 derivatives or molecules mimicking FGF21 action appear to be interesting candidates for the development of novel anti-obesity drugs designed to increase energy expenditure. Highlights: FGF21 causes weight loss by increasing energy expenditure in pre-clinical models. FGF21 induces the "browning" of white fat and enhances brown adipose tissue activity. Serum FGF21 levels are associated with brown adipose tissue activity in humans. High levels, but reduced action, of FGF21 occur in obesity and diabetes. FGF21-based therapy is a promising strategy to treat diabetes, obesity and dyslipidemia.